(untitled) (Hematology Meeting Reports, 2009)
Alkylating chemotherapy agents are used with considerable success to treat numerous human malignancies, including lung cancer, breast cancer, Hodgkin lymphoma and multiple myeloma. Alkylating agents encompass a broad range of structurally diverse agents that includes nitrogen mustards, methylating agents, platinating agents and nitrosoureas.